PERANCANGAN KARTU IDENTITAS BEROBAT ELEKTRONIK MENGGUNAKAN VISUAL STUDIO 2010 DI RSKGM KOTA BANDUNG - Renaldi Luhung; Erix gunawan; Cahyadi agustin (POLITEKNIK PIKSI GANESHA, 2022)
In this day and age technology is growing and increasingly advanced in all fields, as well as in the health sector, namely hospitals. Not a few of them still have shortcomings, such as one of them, namely the Medical Identity Card (KIB), which is still not efficient enough to be applied in hospitals. The identity card for treatment at this hospital still uses a printed sticker affixed to the card, then there is no barcode printed on the identity card for treatment. Therefore, it is still less effective if used in hospitals because it is not uncommon for the stickers attached to come off and disappear on the card. In the absence of a special program for making electronic medical identity cards, it is still necessary to design a better electronic medical identity card. Therefore, this study aims to design an electronic medical identity card using a visual studio, with the aim of making the medical identity card more effective and modern to be applied in hospitals. Keywords: Designer; Medical Identity Card; visual studio 2010